Review of the traditional approaches to modern language teaching and learning methods (Eurasian Research Bulletin, 2023)
In this article, a review of traditional approaches to modern language teaching and learning methods, the use of modern information technologies in the process of language learning and teaching, technical tools and technologies used in the educational process are described in detail.